Liquor ammonia mediated V(v) insertion in thin Co3O4 sheets for improved pseudocapacitors with high energy density and high specific capacitance value. Issue 88 (18th September 2015) - Sahoo, Ramkrishna; Roy, Anindita; Dutta, Soumen; Ray, Chaiti; Aditya, Teresa; Pal, Anjali; Pal, Tarasankar
Abstract : Fabrication of ultrathin 2D Co3 V2 O8 nanosheets for pseudocapacitors, with high specific capacitance value, high energy density and excellent rate capability. Abstract : Ultrathin 2D Co3 O4 and Co3 V2 O8 nanosheets have been produced from our modified hydrothermal technique (MHT). Both the materials have been proved to be extraordinary electrode materials for pseudocapacitors. The neat nanosheets of Co3 O4 and Co3 V2 O8 exhibit a record specific capacitance value of 1256 F g −1 and 4194 F g −1 at 1 A g −1 current density, respectively.